Towards Mirror-Less Graphene-Based Perfect Absorbers - Lee, Sangjun; Kim, Sangin (Applied Sciences (Switzerland), 2023)
Owing to its exceptional electronic and optical properties, graphene has attracted extensive attention among researchers in the development of high-performance optoelectronic devices. However, the light absorption of pure graphene is very poor, limiting its development in practical application. In this review, as a solution for this issue, various types of graphene-based perfect absorbers are addressed in terms of their operation principles and design requirements. Their recent progress and potential applications such as photodetectors and modulators are also discussed. In particular, we emphasize the importance of mirror-less (in particular, one-port mimicking) perfect absorber design due to simplified fabrication processes or enhanced tolerance for fabrication error.
Keywords: graphene; mirror-less; perfect absorption; tunable absorption